2015
DOI: 10.2967/jnumed.114.152496
|View full text |Cite
|
Sign up to set email alerts
|

Claudin-4 SPECT Imaging Allows Detection of Aplastic Lesions in a Mouse Model of Breast Cancer

Abstract: The expression of claudin-4, a protein involved in tight junction complexes, is widely dysregulated in epithelial malignancies. Claudin-4 is overexpressed in several premalignant precursor lesions, including those of cancers of the breast, pancreas, and prostate, and is associated with poor survival. A noncytotoxic C-terminal fragment of Clostridium perfringens enterotoxin (cCPE) is a natural ligand for claudin-4. Here, we demonstrate wholebody quantitative SPECT imaging of preneoplastic breast cancer tissue u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 23 publications
2
20
0
Order By: Relevance
“…However, for noninvasive diagnostic detection, fluorescence‐based imaging is limited by penetration depth and autofluorescence. As an alternative, 111 In radiolabeled cCPE and single‐photon emission computed tomography were used to detect Cldn4 + MDA‐MB‐468 xenograft and other tumors in mice . Here, the radiation exposure has to be considered as a drawback.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, for noninvasive diagnostic detection, fluorescence‐based imaging is limited by penetration depth and autofluorescence. As an alternative, 111 In radiolabeled cCPE and single‐photon emission computed tomography were used to detect Cldn4 + MDA‐MB‐468 xenograft and other tumors in mice . Here, the radiation exposure has to be considered as a drawback.…”
Section: Discussionmentioning
confidence: 99%
“…As an alternative, 111 In radiolabeled cCPE and single-photon emission computed tomography were used to detect Cldn4 + MDA-MB-468 xenograft and other tumors in mice. 52 Here, the radiation exposure has to be considered as a drawback.…”
Section: The Cldn4 Biosensor Comprises An Avidin-conjugated Ccpe Targmentioning
confidence: 99%
“…Among the 27 family members, CLDN‐3 and ‐4 are the CLDNs most frequently overexpressed in malignant tumors, and their expression levels are well correlated with tumor malignancy . Fluorescence‐conjugated C‐CPE has been used to visualize small, early‐stage lesions that are difficult to identify through conventional diagnostic methods . Therefore, a method for detecting CLDNs in biopsy and cytology samples has received attention as a potential diagnostic tool .…”
Section: Cldn‐4 As a Target For Cancer Therapymentioning
confidence: 99%
“…13,14 Fluorescence-conjugated C-CPE has been used to visualize small, early-stage lesions that are difficult to identify through conventional diagnostic methods. [66][67][68] Therefore, a method for detecting CLDNs in biopsy and cytology samples has received attention as a potential diagnostic tool. 69,70 In this context, antibody 5A5 (which recognizes CLDN-3 and -4, but not CLDNs-1, -2, -5, -6, -7, -9, and -10) preferentially accumulated more than control IgG in tumor tissue (Fig.…”
Section: Cldn-4 As a Target For Cancer Therapymentioning
confidence: 99%
“…Interestingly, although the full-length CPE is highly toxic when injected intravenously in animals, the carboxi-terminal fragment (i.e., the C-terminal 30aa) of CPE, is devoid of any toxicity while sufficient for binding to its receptors(11). Accordingly, several strategies have been developed that used the c-CPE as a tumor-specific carrier for diagnostic and therapeutic agents(12, 13). Importantly, recent data from our research group showed that c-CPE conjugated to the NearInfraRed-Dye CW800 is highly effective in identifying microscopic/metastatic ovarian tumor in the abdomen of mice harboring ovarian cancer xenografts(12, 14).…”
Section: Introductionmentioning
confidence: 99%